2017
DOI: 10.1002/elan.201700366
|View full text |Cite
|
Sign up to set email alerts
|

Metallophthalocyanines Bearing Polymerizable {[5‐({(1E)‐[4‐(Diethylamino)phenyl]methylene}amino)‐ 1‐naphthy1]oxy} Groups as Electrochemical Pesticide Sensor

Abstract: The synthesis and characterization of novel metallophthalocyanines (MPcs(ea)) carrying {[5‐({(1E)‐[4‐(diethylamino)phenyl]methylene}amino)‐1‐naphthyl]oxy} groups on four peripheral positions have been reported. These complexes have been characterized by a combination of FT‐IR, 1H and 13C NMR, mass and UV‐Vis spectroscopy techniques. Redox active metal centers in the core of the Pc rings (Co (II) [CoPc(ea)], Mn(III) [Cl–MnPc(ea)], and Ti(IV)O [TiOPc(ea)]) and electropolymerizable substituents on the peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…As shown in Figure S11 (Supporting Information), when the cathodic potentials of TC ‐CoPc were scanned in TBAPF/DMF electrolyte system, the characteristic signals of [Co II Pc 2− ]/[Co I Pc 2− ] 1− and [Co I Pc 2− ] 1− /[Co I Pc 3− ] 2− were observed at −0.28 V vs saturated calomel electrode (SCE) and −1.30 V vs SCE, respectively. [ 13 ] Moreover, the controlled compound TE ‐CoPc gave similar redox peaks at −0.29 V vs SCE and −1.30 V vs SCE. The result was very close to that of unmodified CoPc, indicating the similar electronic effects of TE ‐CoPc and TC ‐CoPc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure S11 (Supporting Information), when the cathodic potentials of TC ‐CoPc were scanned in TBAPF/DMF electrolyte system, the characteristic signals of [Co II Pc 2− ]/[Co I Pc 2− ] 1− and [Co I Pc 2− ] 1− /[Co I Pc 3− ] 2− were observed at −0.28 V vs saturated calomel electrode (SCE) and −1.30 V vs SCE, respectively. [ 13 ] Moreover, the controlled compound TE ‐CoPc gave similar redox peaks at −0.29 V vs SCE and −1.30 V vs SCE. The result was very close to that of unmodified CoPc, indicating the similar electronic effects of TE ‐CoPc and TC ‐CoPc.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S11 were observed at −0.28 V vs saturated calomel electrode (SCE) and −1.30 V vs SCE, respectively. [13] Moreover, the controlled compound TE-CoPc gave similar redox peaks at −0.29 V vs SCE and −1.30 V vs SCE. The result was very close to that of unmodified CoPc, indicating the similar electronic effects of TE-CoPc and TC-CoPc.…”
Section: Roles Of Amphiphilic Tc-copcmentioning
confidence: 92%
“…The cobalt complex is obtained and used as a mixture of the different regioisomers, which exhibit identical electronic and steric properties 36,37 , and CoPc2 thus gives a unique electrochemical signature (Supplementary Fig. 1) with three reversible Faradaic waves that could be assigned to the Co II /Co I redox couple and to ligand reduction peaks 38,39 . With relatively low catalyst loadings of CoPc2 dispersed into porous films of carbon black powder or carbon nanotubes on a carbon paper cathode, the modified electrode functions as highly effective CO 2 RR electrocatalysts in acidic (pH 4), neutral (pH 7.3), and basic conditions (pH 14).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, electrochemical features of diethylamino groups are significant. In literature showed that the introduction of diethylamino groups into the peripheral/nonperipheral positions of phthalocyanines increased the electrochemical and electropolymerization properties of phthalocyanines [24][25][26][27]. Here, we wondered how the presence of phthalocyanines in the non-peripheral positions of the diethylamino group affects the electrochemical properties of phthalocyanine compounds.…”
Section: Introductionmentioning
confidence: 99%